Improving Mathematical Communication - Feylosofia Putri Agry; Kartono Kartono; Masrukan Masrukan (Universitas Negeri Semarang, 2021)
This research was conducted due to the lack of mathematical communication skills among prospective elementary school teachers. Knowing the mathematics communication skills of prospective elementary school teachers is the aim of this study. The method used is descriptive qualitative. The subjects used in this study were 6 semester 1 students in the basic concepts of mathematics subject. The data collection uses questions related to Combination material with 6 items related to mathematical communication skills.